Odpowiedzi

2009-11-27T13:58:13+01:00
Rozumiem że ^ znaczy mnożyć więc

a)3^x+2 +9^x+1=810
3x+2+9x+1=810
12x=810-3
12x=807
x=67.25

b)(2-√3)^x + (2+√3)^x= 4
2x-√3x+2x+√3x=4
4x=4(pierwiastki sie skrócą)
x=1

c)5^x+ 5^3-x =30
5x+15-x=30
4x=15
x=3.75

d)3^x+1 + 18*3^-x= 29
3x+1+54^(-x)=29
3x-54x=28
-51x=28
x=-28/51
x≈-0.55
1 1 1
Najlepsza Odpowiedź!
2009-11-27T17:51:10+01:00
A)3^x+2 +9^x+1 =810
3^x * 3^2 + 3^2(x+1)=810
3^x *9 + 3^2x * 3^2=810 /:9
3^x + 3^2x=90
3^x=b dla b>0
b+b^2-90=0
Δ=1-4*(-90)=1+360=361
√Δ=19
b₁=(-1-19)/2=-20/2=-10 <0
b₂=(-1+19)/2=18/2=9

3^x=9
3^x=3^3
x=3

b)
(2-√3)^x + (2+√3)^x= 4
(2-√3)^x +[(2+√3)^x * (2-√3)^x]/[(2-√3)^x]=4
(2-√3)^x +[(2-√3)*(2+√3)]^x/[(2-√3)^x]=4
(2-√3)^x +[(4-3)^x]/[(2-√3)^x]=4
[(2-√3)^2x +1]/[(2-√3)^x]=4 /*(2-√3)^x
(2-√3)^2x +1=4*[(2-√3)^x]
(2-√3)^x =b
b^2 -4b +1=0
Δ=16-4=12=4*3
√Δ=2√3
b=(4-2√3)/2=(2-√3)
b=(4+2√3)/2=(2+√3)
(2-√3)^x=(2-√3)
x=1


c)
5^x+ 5^3-x =30
5^x+5^3 * 5^-x =30
5^x+ 125/(5^x) =30 /* (5^x)
5^2x -30(5^x) +125=0
5^x=b dla b>0
b^2 -30b +125=0
Δ=900-4*125=900-500=400
√Δ=20
b=(30-20)/2=10/2=5
b=(30+20)/2=50/2=25

5^x=5
x=1

5^x=25
5^x=5^2
x=2


d)
3^x+1 + 18*3^-x= 29
3^x *3 +18/(3^x)=29 /*(3^x)
3^2x *3 +18-29*(3^x)=0
3^x=b dla b>0
3b^2-29b+18=0
Δ=841-4*3*18=841-216=625
√Δ=25
b=(29-25)/6=4/6=2/3
b=(29+25)/6=54/6=9
3^x=9
3^x=3^2
x=2